(untitled) (LACCEI, 2024)
The objective of the research was to determine the impact of tax planning on compliance with tax obligations of a small company dedicated to construction, during the periods 2017-2019. The methodology used was a quantitative, cross-sectional, explanatory level, non-experimental design, and linear type with a single observation group in terms of its contrast technique. The analyzed information consisted of the accounting and tax documents and reports of the company during the study period. The results show that due to a lack of knowledge of tax regulations, contingencies occurred in 2017, such as choosing the wrong tax regime, late filing of monthly tax returns, inadequate record keeping, and other formal obligations, obtaining a "moderate" compliance rating (78%) according to the proposed scale. After implementing tax planning, detected deficiencies were improved and regularized, and outstanding debts were settled. As a result, the tax burden was optimized, and "very high" compliance percentages were achieved, 88% and 94% for the 2018 and 2019 periods, respectively. It was demonstrated that tax planning has a significant impact on the company’s tax burden compliance with positive variations of 25.8% (2018) and 29.7% (2019) compared to 2017 Therefore, the hypothesis was confirmed.